UPAYA MENINGKATKAN MENULIS TEKS EKSPLANASI MENGGUNAKAN METODE STAD PADA SISWA KELAS VIII SMP NEGERI 6 CIKALONGKULON - dede hamimudin (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The purpose of this study was to see the learning activities of students and teachers with the application of the STAD method when learning written explanatory text. Also to see significant fears between before and after using the STAD method in an effort to improve explanatory text writing skills. The samples taken were 26 students from class VIII SMP Negeri 6 Cikalongkulon. The data sets used were the lesson plan (RPP), the observation sheet and the test sheet. The final results of the pretest and posttest there are differences and improvements in writing explanatory text skills using the STAD method in class VIII students of SMP Negeri 6 Cikalongkulon. The results of this study can develop an environment that writes explanatory text using the STAD method in class VIII students of SMP Negeri 6 Cikalongkulon. The results of teacher observations in the classroom during the learning process were 80% carried out and 75% of the students' learning processes were carried out. From the learning results, the improvement of explanatory text writing skills using the STAD method in class VIII students of SMP Negeri 6 Cikalongkulon, and improved according to the expected research objectives.